Advances in Rock Mechanics and Geotechnical Engineering Volume I - Hasanipanah, Mahdi; Armaghani, Danial Jahed; Zhou, Jian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue entitled "Advances in Rock Mechanics and Geotechnical Engineering" is devoted to the publication of the latest research, field works, and laboratory investigations in the area of rock mechanics and geotechnical engineering. This Special Issue has published novel contributions in different areas of geotechnical and geomechanical engineering such as slope and embankment, tunneling and underground space technologies, pile and foundation, rock mechanics and rock blasting, excavation and leveling projects, ground improvement techniques, unsaturated soil, practical issues in soft soil, mining technology, geo-environmental engineering, new laboratory testing, applied geology for construction, and novel geotechnical construction methods. The focus of this reprint is on the development of computational methods for solving problems in the fields of rock mechanics and geotechnical engineering.